Targeting the HIF-1α/Cav-1 Pathway with a Chicory Extract/Daidzein Combination Plays a Potential Role in Retarding Hepatocellular Carcinoma - Zakaria, Sherin; Nawaya, Reem; Abdel-Hamid, Nabil M.; Eldomany, Ramadan A.; El-Shishtawy, Mamdouh M. (Current Cancer Drug Targets, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most rapidly growing solid cancers, that is characterized by hypoxia. Hypoxia-inducible factor-1α (HIF-1α) is a transcription factor that regulates tumor proliferation and metastasis. It induces caveolin-1 (Cav-1) expression, a glycoprotein found on the membrane surface, then Cav-1 triggers angiogenesis and metastasis in HCC. Objective: We hypothesize that targeting HIF-1α and consequently, Cav-1 using the antioxidant natural compound such as chicoric acid and a Cav-1 inhibitor daidzein (DAZ) could be a useful approach in the management of HCC. This study was conducted to investigate the possible therapeutic efficacy of standardized chicory leaf extract (SCLE) and DAZ via modulation of HIF-1α and Cav-1 in HCC rats. Methods: Diethyl nitrosamine (DENA) was used for HCC induction. After the induction period, four groups (10 rats for each) were treated with SCLE, DAZ, a combination of both, as well as sorafenib, all compared to the non-treated control. We assessed hepatic HIF-1α protein expression, Cav-1 gene expression, serum level of AFP, hepatic tissue content of VEGF, MMP-9, oxidative stress markers MDA and SOD. Results: DAZ, SCLE, and their combination, significantly down-regulated the expression of HIF-1α, Cav-1, and consequently dampened MMP-9, VEGF, hepatic content. It has been observed that the combination treatment showed a synergistic effect compared to either treatment alone. Importantly, the combination treatment exhibited a significantly more potent effect than sorafenib. Conclusion: This study showed the potential role of the HIF-1α/Cav-1 pathway in HCC progression, moreover, SCLE and DAZ showed a potent efficacy in retarding HCC via modulation of this pathway.
Keywords: daidzein